No-till, crop residue management and winter wheat-based crop rotation strategies under rainfed environment - Nurbekov, Aziz; Kosimov, Muhammadjon; Islamov, Sokhib; Khaitov, Botir; Qodirova, Dilrabo; Yuldasheva, Zulfiya; Khudayqulov, Jonibek; Ergasheva, Khafizakhon; Nurbekova, Ruhangiz (Frontiers in Agronomy, 2024)
Rainfed agriculture is primarily limited by unstable low precipitation, poor soil fertility and monocropping, which are the main factors leading to decreased crop production. This long-term research was conducted under a rainfed agroecosystem from 2019 to 2023 on the sierozem soil of the Karshi steppe, Uzbekistan. Along with winter wheat (WW) which was the main crop covering 50% of each proposed cropping pattern, chickpea (CH), safflower (SA), flax (FL), barley (BA) and canola (CA) were evaluated to find the most suitable rotation systems under no-till (NT) i.e. NT1: WW–CH–WW–FL, NT2: CH–WW–SA–WW, NT3: WW–SA–WW–BA and NT4: SA–WW–CA–WW compared against continuous WW produced with conventional tillage (CT). Results showed that the integrated effect of NT x crop diversification x residue retention positively affected crop productivity; however, their impact were significantly higher under the NT2 treatment, but not with continuous WW under CT. The highest grain yield of WW in the 2020-2021 growing season was recorded under NT2 and NT4 treatments with values of 1.47 and 1.30 Mg ha-1, while the lowest index (1.02 Mg ha-1) was found at the CT treatment. The grain yield in the NT treatments increased with the improvement of soil chemical and physical parameters, i.e. NPK and humus content. When comparing NT2 to CT treatment at the project end, the total N, P, and K values at the 0–20 cm soil profile were 27.9%, 13.9%, and 33.9% higher, respectively. This study concluded that implementation of NT along with strategic selection of legumes incorporated into the cropping system and residue management can be prioritized as rehabilitation measures in rainfed croplands.